Influence of YBa2HfO5.5 – 'derived secondary phase' on the critical current density and flux-Pinning force of YBa2Cu3O7−δ thick films. (December 2015) - Rejith, Pullanhiyodan Puthiyaveedu; Vidya, Sukumariamma; Thomas, Jijimon Kumbukkattu
Highlights: Effect of addition of different weight percentages of nano HfO2, BaHfO3 and YBa2 HfO5.5 prepared through modified combustion method in YBa2 Cu3 O7−δ thick films was studied. The microstructure of the samples showed the formation of a secondary phase YBa2 HfO5.5 without deteriorating its superconducting properties. The variation of Tc, magnetic field dependence of critical current density and flux pinning force of YBa2 Cu3 O7−δ thick films with addition of HfO2, BaHfO3 and YBa2 HfO5.5 were studied. The Jc in the YBa2 Cu3 O7−δ – HfO2, BaHfO3 and YBa2 HfO5.5 samples is attributed to the presence of the insulating and non-reacting YBa2 HfO5.5 phase as artificial pinning center. Abstract: Enhancement in critical current density ( Jc ) and flux pinning force ( Fp ) in superconducting thick films of YBa2 Cu3 O7−δ (YBCO) added with small quantities of nanopowders of HfO2, BaHfO3 and YBa2 HfO5.5, coated on YBa2 ZrO5.5 substrate by dip-coating technique is reported. Critical current density measurements were done over an applied magnetic field using standard four probe technique and the results are compared with that of pure YBCO. High critical current density ( Jc ) of ∼4.84 MA/cm 2 at 77 K in self-field was obtained for 2 wt% of YBa2 HfO5.5 added YBCO. A systematic increase in Jc observed in YBCO films prepared by the addition of nano HfO2, BaHfO3 and YBa2 HfO5.5, attributed to the formation of a non-reacting 'derived secondary phase' YBa2 HfO5.5 (YBHO) in the YBCO matrix. YBCO–YBa2 HfO5.5 composite thick films have showed eightfold increases in Jc (3.29 MA/cm 2 ) at 77 K and 0.4 T compared to pure YBa2 Cu3 O7−δ film (0.37 MA/cm 2 ), while maintaining a high transition temperature ( Tc ). The development of effective pinning centers in nano particle added YBCO thick film have enhanced the flux pinning force from 1.8 GN/m 3 for pure YBCO to a maximum value of 13.15 GN/m 3 for YBCO–YBa2 HfO5.5 . X-ray diffraction and energy dispersive spectroscopic analysis confirmed the presence of secondary phase, derived in the matrix.